2015
DOI: 10.1200/jco.2014.55.5789
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled, Multicenter Phase II Study of the Efficacy and Safety of Apricoxib in Combination With Either Docetaxel or Pemetrexed in Patients With Biomarker-Selected Non–Small-Cell Lung Cancer

Abstract: Purpose Overexpression of COX-2 correlates with advanced stage and worse outcomes in non–small-cell lung cancer (NSCLC), possibly as a result of elevated levels of COX-2–dependent prostaglandin E2 (PGE2). Exploratory analyses of studies that used COX-2 inhibitors have demonstrated potentially superior outcome in patients in whom the urinary metabolite of PGE2 (PGE-M) is suppressed. We hypothesized that patients with disease defined by PGE-M suppression would benefit from the addition of apricoxib to second-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 12 publications
(8 reference statements)
1
35
0
Order By: Relevance
“…A criticism regarding the study is that a 50% decline in urinary PGEM levels was a low threshold with which to identify patients with tumors that could benefit from COX‐2 inhibitors. Similar results were observed by Edelman et al when apricoxib was combined with chemotherapy in patients with recurrent NSCLC who experienced a decline in urinary PGEM levels after a run‐in period . Edelman et al recently reported the results of a randomized phase 3 study evaluating the addition of celecoxib to frontline platinum‐based chemotherapy in patients with tumors that had elevated COX‐2 expression .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…A criticism regarding the study is that a 50% decline in urinary PGEM levels was a low threshold with which to identify patients with tumors that could benefit from COX‐2 inhibitors. Similar results were observed by Edelman et al when apricoxib was combined with chemotherapy in patients with recurrent NSCLC who experienced a decline in urinary PGEM levels after a run‐in period . Edelman et al recently reported the results of a randomized phase 3 study evaluating the addition of celecoxib to frontline platinum‐based chemotherapy in patients with tumors that had elevated COX‐2 expression .…”
supporting
confidence: 71%
“…Similar results were observed by Edelman et al when apricoxib was combined with chemotherapy in patients with recurrent NSCLC who experienced a decline in urinary PGEM levels after a run-in period. 28 Edelman et al recently reported the results of a randomized phase 3 study evaluating the addition of celecoxib to frontline platinum-based chemotherapy in patients with tumors that had elevated COX-2 expression. 29 This study was based on a randomized phase 2 study conducted by the same investigators that demonstrated an improvement in survival with the addition of celecoxib in patients with tumors that had elevated COX-2 expression.…”
mentioning
confidence: 99%
“…Another phase II study in previously untreated COX-2-positive advanced NSCLC patients showed therapeutic benefit to COX-2 inhibition in combination with platinum-based chemotherapy (Wang et al, 2008). A larger study however employing various biomarkers of COX activity and target engagement have reported no meaningful clinical benefit, highlighting the need for more specific strategies for targeting prostaglandin accumulation (Edelman et al, 2015). For example, the development of agents that lower the cellular levels of 15-d-PGJ2 or specifically inhibit 15-d-PGJ2 may constitute a useful approach for the chemosensitization of KRAS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, COX-2 inhibitors showed a synergistic effect with docetaxel on NSCLC cell line. However, in a recent phase II clinical trial the combination of docetaxel and apricoxib (COX-2 inhibitor) as second-line therapy on advanced NSCLC patients, showed negative results, implying that taxanes-driven augmentation of COX-2 expression might diminish the effect of COX-2 inhibitors [61].…”
Section: Discussionmentioning
confidence: 99%